APPLICATION OF TGT COOPERATIVE LEARNING MODEL IN ANGLE LEARNING IN ELEMENTARY SCHOOL - brigita theoananta; muadhatus solehah; putri sahapani; rendo fahestama; muhammad daffa diyah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2025)
The application of TGT (Team Games Tournament) to corner material allows learners to explore these concepts collaboratively, with game support designed to strengthen their understanding. In addition, this model also contributes to the development of students' social skills, such as cooperation, communication, and mutual respect for each other's opinions. The author uses the literature study method in conducting research. The author also uses a descriptive method in describing the data that has been obtained. The results and discussions we got The implementation of the TGT (Teams Games Tournament) type cooperative learning model proved to be effective in increasing students' understanding and activeness in learning corner material in elementary school The TGT model involved students in small groups to cooperate, play, and compete through academic tournaments. This helps to increase material understanding, motivation, participation, and students' social skills. Various studies show that the use of TGT in corner learning is effective in improving learning outcomes and student motivation. The application of TGT encourages students to collaborate, compete healthily, and understand concepts through activities that are relevant to daily life.